Multilingualism in South African universities is a fallacy : a critical realist perspective - Modiba, Mokgadi Asnath; Emsley, Maletšema Ruth (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
This paper explores the empirical, real, and actual trajectories in South African universities regarding multilingualism and decolonisation. It employs the critical realist approach to uncover these trajectories through reviewed literature. It investigates whether the policy is followed in implementing African indigenous languages (AILs) against the hegemony of English and Afrikaans in South African universities. The paper found that multilingualism is still an area that requires attention, even though ample legislation and policies were drafted to necessitate decolonised practices that foster it. This paper argues that the notion of decolonisation and the use of multilingualism can be placed at the centre of curriculum transformation. However, the paper again argues that actual events like a disconnect between basic and higher education systems, digitalisation, intellectualisation of African languages and confidence of the African language users in the academia can hinder multilingualism. African learners come to universities with unique African language repertoires, but English is still mostly used as a medium of instruction in most South African universities. This paper makes recommendations that can rescue the situation, some of them which are funding African languages digitalisation, awarding African languages research outputs, and widely conducting studies on the African students and academics’ perceptions on multilingual education.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: African indigenous languages; Decolonisation; Epistemologies; Language policy; Medium of instruction; Multilingualism; Imperialism; Education, Higher -- South Africa